Sound absorption properties of a sunflower composite made from crushed stem particles and from chitosan bio-binder. (October 2016) - Mati-Baouche, Narimane; de Baynast, Hélène; Michaud, Philippe; Dupont, Thomas; Leclaire, Philippe
Highlights: A sunflower stem particles/chitosan 100% bio-based material was built. The sound absorption coefficient and transmission loss were measured. The acoustic properties were also studied theoretically. Kinematic and dead-end porosity were measured. Dead-end pores and clusters appear as peculiarities of the studied material. Abstract: A recent study investigated the mechanical, thermal and acoustical properties of a bio-based composite made from crushed particles of sunflower stalks binded together by chitosan, a bio-based binder. The acoustical performance in absorption was found to be poor as the material was highly compacted and with low porosity. The present study focuses on the acoustical properties of a higher porosity composite, with lower density while the mechanical rigidity remains fairly high. A higher absorption coefficient is obtained. The experimental results on the absorption coefficient are compared to the prediction of a model involving 5 physical parameters (porosity, tortuosity, airflow resistivity, thermal and viscous characteristic lengths). The characterization methods to determine these parameters are described. The comparison between experimental and theoretical results shows that this material exhibits peculiar microstructural features. It is found that the sound absorption properties can involve dead-end pores or clusters and multiple porosity scales in the material.